Tectonic Activity Phases of Cenozoic Period in Xuat Hoa Area, Bac Kan Province, Northeast Region, Vietnam - Phi, Truong Thanh (Indonesian Journal on Geoscience, 2019)
DOI: 10.17014/ijog.6.3.311-325This paper presents the analytical results of a hundred and three striations from twenty-five survey locations along 3B highway in Xuat Hoa area, Bac Kan Province, Vietnam. The analytical results have determined four main phases of tectonic activity: NW−SE, E−W, NE−SW, and N−S. The first phase, the compressive stress state in the direction of NW−SE, caused the right lateral strike-slip motion of faults in the direction of E−W and the left lateral strike-slip motion of faults in the direction of N−S. The second phase, the compressive stress state in the direction of E−W, caused the left lateral strike-slip motion of faults in the direction of NW−SE and the right lateral strike-slip motion of faults in the direction of NE−SW. The third phase, the compressive stress state in the direction of NE−SW, caused the left lateral strike-slip motion of faults in the direction of E−W and the right lateral strike-slip motion of faults in the direction of N−S. The final phase, the compressive stress state in the direction of N−S, caused the left lateral strike-slip motion of faults in the direction of NE−SW and the right lateral strike-slip motion of faults in the direction of NW−SE. In addition, these stress states also created thrust faults in the directions of NE−SW, N−S, NW−SE, and E−W. Based on the analytical results, field investigation, and previous studies, this study proposes the order of the main compressive stress states in the directions of 1) NW−SW, 2) E−W, 3) NE−SW, and 4) N−S.